University or polytechnic? : A fuzzy-set approach of prospective students' choice and its implications for higher education institutions' managers - Henriques, Paulo Lopes (2022)
This study aims to provide a deeper knowledge of the factors behind undergraduates' choice of an higher education institution (HEI) in Portugal. Based on Chapman's model (1981), this study presents the results of a survey on the personal characteristics and institutional drivers that influence this choice. The survey results in a sample of 368 Portuguese secondary or vocational education students in their final year who intend to apply to a public HEI. To the best of the authors' knowledge, this study is the first to apply the fuzzy-set qualitative comparative analysis to this field of study. The findings indicate that the choice criteria of prospective students are the same irrespective of whether they are applying to a university or a polytechnic school. Among the criteria, job opportunities and the institution's reputation are the most important. Thus, managers should account for these criteria when seeking to increase their institution's competitive advantage.